Peran Guru dalam Implementasi Metode Joyful Learning pada Pembelajaran Huruf Hijaiyah di RA Al Muslihun - Safira Safira; Muhamad Ridwan; Sahrin Djalia (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study discusses the role of teachers in the implementation of the joyful learning method in hijaiyah letter learning in Raudhatul Athfal (RA) Al Muslihun. The purpose of this study is to analyze the role of teachers in the application of the joyful learning method in hijaiyah letter learning, identify the form of implementation of the joyful learnig method, and identify obstacles faced in its implementation. The background of this research is based on the low ability of students to recognize and pronounce hijaiyah letters correctly, so a fun and effective learning method is needed. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of this study show that teachers have an important role as facilitators, motivators, and innovators in educational games, as well as interactive methods. The form of implementation of joyful learning in learning hijaiyah letters is carried out through letter card games and the use of interesting visual media. However, there are several obstacles such as limited learning media, students' abilities and limited learning time. Therefore, teachers' creativity and adequate support of facilities and infrastructure are needed to optimize the application of these methods.